2000
DOI: 10.1111/j.1475-2743.2000.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching from arable and horticultural land

Abstract: Arable crops in the UK make a large contribution to nitrate leaching by virtue of the land area they cover (>4.5 million ha). By contrast horticultural crops occupy only a small area (< 0.2 million ha) but can leach very large amounts of nitrogen. The application of nitrogen fertilizer to arable and horticultural crops is very cost-effective, stimulating its use. MAFF's Nitrate Research Programme for arable and horticultural crops aims to reduce nitrate leaching and maintain productive farming through Best Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(115 citation statements)
references
References 71 publications
(33 reference statements)
0
107
0
5
Order By: Relevance
“…Integrated systems have no specific mechanisms that optimize nutrient efficiency and minimize environmental impacts other than the careful and, perhaps, suboptimal use of inputs. As our description of the complexity of soil nutrient dynamics shows, suboptimal applications cannot guarantee better NUE: a graph of average losses of nitrate by leaching from the Broadbalk experiment (Goulding 2000) shows that these are reduced by applying suboptimal rates of N fertilizer, but so are yields. The skill of the land manager is critical, as explained in §5e.…”
Section: Farm Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated systems have no specific mechanisms that optimize nutrient efficiency and minimize environmental impacts other than the careful and, perhaps, suboptimal use of inputs. As our description of the complexity of soil nutrient dynamics shows, suboptimal applications cannot guarantee better NUE: a graph of average losses of nitrate by leaching from the Broadbalk experiment (Goulding 2000) shows that these are reduced by applying suboptimal rates of N fertilizer, but so are yields. The skill of the land manager is critical, as explained in §5e.…”
Section: Farm Systemsmentioning
confidence: 99%
“…However, just as the earlier policies to drive food production caused unwanted, and probably unexpected pollution, so these later policies have had unwanted and unexpected consequences: rotational Set-aside is a prime cause of nitrate leaching (Goulding 2000) and whole-farm models that integrate all inputs to and outputs from farms suggest that practices to decrease one loss can increase others, e.g. practices that reduce nitrate leaching on arable farms, and those that reduce ammonia volatilization on livestock farms, can increase other environmental impacts such as denitrification and nitrous oxide emissions and P build-up in soils (Bergströ m & Goulding 2005).…”
Section: Policy and Nutrient Managementmentioning
confidence: 99%
“…However, upon transfer from the grassland phase to the arable phase, large quantities of mineral N are released, following ploughing in of the grass sod (Nevens and Reheul 2002). This phase should be managed carefully, as it may lead to high rates of nitrate leaching (Whitmore et al 1992;Francis 1995;Hoffman 1999;Goulding 2000;Eriksen 2001). To prevent mineral N levels exceeding the potential uptake capacity of maize, the N fertilizer dose for first year maize should be corrected for the expected release from the ploughed-in grass.…”
Section: Limiting the Intensity Of Internal N-fluxesmentioning
confidence: 99%
“…Loss through leaching is a common way for N to be lost from fertilizer, resulting in potential groundwater pollution (Goulding 2000). Previous studies have indicated that wood-or manure-based biochars can reduce leaching of fertilizer N in highly weathered subtropical or tropical soils using pot experiments (Lehmann et al 2003), repacked soil columns (Laird et al 2010;Singh et al 2010;Kameyama et al 2011) or suction cup lysimeters in fields (Steiner et al 2008;Major et al 2011).…”
Section: Introductionmentioning
confidence: 99%